Evaluating the water quality of Tietê River, São Paulo State, Brazil, during the COVID-19 period - de Araujo, I. G. [UNESP]; Bonotto, D. M. [UNESP] (Springer Nature, 2025)
The Tietê River is the main river that flows entirely within the state of São Paulo, Brazil. Its dynamics are historically connected to activities from the colonial period in São Paulo, known as the Bandeiras, and extend to the urbanization and social development processes of municipalities along its banks. This study focuses on the hydrochemistry of the surface waters of the Tietê River by analyzing samples collected along its course, from its source in Salesópolis city to its confluence with the Paraná River in Itapura city. The survey was conducted in the summer of 2021/2022, during the period affected by the Coronavirus disease 2019 (COVID-19). The results were compared with reported data for the post-COVID-19 period and with the threshold values established by two official Brazilian agencies responsible for water quality regulation: (1) Ordinance No. 888/21 of the Brazilian Ministry of Health and (2) CONAMA Resolution No. 357/2005. The data indicated high levels of chloride, nitrate, nitrite, phosphate, sodium, and total dissolved solids (TDS) occurring in the following sites: (1) municipalities of the Metropolitan Region of São Paulo city (MRSP); (2) confluence of the Tietê River with its tributary Sorocaba River, at Laranjal Paulista city. The hydrogeochemical diagrams of Piper, Schoeller, and Stiff allowed define the major facies of the Tietê River waters, as well as plotting their changes along its course up to the mouth. The Water Quality Index (WQI) was a useful tool for indicating better water quality at the source and mouth of the Tietê River, while lower values indicated worse quality at the MRSP and Laranjal Paulista areas. At most monitored sites, the WQI values indicated improved water quality conditions during the COVID-19 period compared to the post-COVID-19 period, likely due to a reduction in anthropogenic inputs of contaminants.